Highly conserved ion binding sites are not all functionally relevant in mouse KCC4 - Becker, Lisa; Hausmann, Jens; Wellpott, Rieke; Hartmann, Anna-Maria (Frontiers in Molecular Biosciences, 2025)
IntroductionThe potassium chloride cotransporter 4 (KCC4) is expressed in various tissues and plays an important role in distal renal acidification and hearing development. Although KCCs transport K+ and Cl− in a 1:1 stoichiometry, two Cl− coordination sites were indicated via cryo-electron microscopy (CryoEM).MethodsIn a comprehensive analysis, we analyzed here the consequences of point mutation of residues coordinating potassium, and chloride in the first (Cl1) and second (Cl2) coordinating site in KCC4 using Tl+ based flux measurements.ResultsSurprisingly, not all highly conserved coordination sites in KCC4 are essential. Three out of five residues (N131, Y216, and T432) are functionally relevant for potassium coordination. For chloride coordination in Cl1, all three residues (G134, V135, and I136) are important, whereas three out of four residues (G433, M435, and Y589) are relevant for chloride binding in Cl2. As all ion coordination sites are important in KCC2, this indicates that there is a certain flexibility in the stringency of ion coordination in KCC4. One possible reason for the different relevance of ion coordination sites could be the large extracellular loop (LEL). The LEL is structured differently within KCCs and is directly linked to the transmembrane domain (TM) 6, where most of the coordination sites reside. Substitution of ion coordination sites in the KCC22-4-2 chimera, in which the LEL from mouse KCC4 is exchanged with the LEL of rat KCC2, have the same effect as substitutions in rat KCC2. An exception is the substitution of the potassium coordination site I111 in TM1, which shows enhanced activity in the KCC22-4-2 chimera compared to the impaired activity in rat KCC2 and not affected activity in mouse KCC4.ConclusionThus, the different relevance of the ion coordination sites between KCC2 and KCC4 cannot be attributed solely to the different structured LEL; other structural elements must also be involved here.